Myelinated-nerve behavior in psoriasis - Lomuto, M. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1995)
The relationship between the nervous system and psoriasis is still unclear. Certain neuropeptides seem to play significant roles, but less is known about the behavior of myelinated nerve fibers. In a group of 26 psoriasis patients motor function was evaluated using bipolar surface electrodes over the median, ulnar and peroneal nerves. Sensorial function was tested along the median, ulnar and sural nerves. Abnormalities were observed in only two patients; one presented a slight reduction in motor conducting velocity of the peroneal nerve; in the second, motor conduction velocity along the peroneal nerve was markedly reduced. There were also moderate reductions in the sensorial conduction velocities of the median and ulnar nerves, and no response could be evoked with sural nerve stimulation. Both sensory and motor parameters were normal in all other patients. There were no correlations between our findings and the patient's PASI index, the presence of arthro-myalgia, the duration of the disease of alcohol-tobacco use. These findings demonstrate the integrity of the peripheral nervous system (at least as far as large fibers are concerned) in psoriasis patients. These large fibers do not appear to play a significant role in this disease.
Keywords: Median nerve; Nerve fibers, myelinated; Neural conduction; Peroneal nerve; Psoriasis; Sural nerve; Ulnar nerve